Log in to add a comment

Log in to add a comment

1. Transform the Quadratic Equation in standard form.

2. Factor the resulting quadratic equation. (Factor the first and last term of the equation, copy the sign of the second term)

3. Apply Zero Product Property by equating both factors to zero.

4. Solve each resulting equation.

5. Check the values of the solution by substituting the solution to the original equation.

Given: 11x+15= -2x²

Standard Form: 2x²+11x+15=0

Then Factor it (Trial and Error Method) (2x+5) (x+3)=0

Solve the 2 x1: 2x+5=0

2x/2= -5/2 (Transpose the +5 to the other side so it will become -5.)

x= -5/2

x2: x+3=0

x= -3 (Transpose the +3 to the other side so it will become -3.)